Putusan Hakim Pengadilan Agama Surabaya Tentang Wasiat Wajibah Bagi Suami Non Muslim Perspektif Hukum Islam - Oming Ratna Wijaya (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2023)
This research highlights the requirements for valid heirs, where both must be Muslim, but in practice, there are cases where non-Muslims can receive or give inheritance through a Wajibah Will, as happened at the Surabaya Religious Court in case number 0124/pdt.P /2022/PA.Surabaya. The aim of this research is to examine the legality of this decision in law and to look at the provisions that support this decision and the basis of Islamic law that underlies this decision. Field research methods with a qualitative approach were used in this research. Data was obtained from secondary and primary data sources, with data collection techniques in the form of observation, interviews and documentation obtained from information and facts regarding the determination of mandatory wills for non-Muslim husbands at the Surabaya Religious Court. Interviews were conducted with the chairman of the Panel of Judges who determined the case. All data were analyzed inductively. The results of the research show the view of Islamic law from the perspective of the Maliki and Hanafi schools which prohibits Wajibah Wills for non-Muslim husbands. However, the views of the Shafi'i and Ahmad ibn Hanbal schools of thought allow it on condition that it meets the established criteria. Regarding the decision of the Panel of Judges in case number 0124/pdt.P/2022/PA.Surabaya, it is based on the Principle of Equality in the Eyes of the Law, which allows this determination to be made by the panel of judges at the Surabaya Religious Court.